Konservasi Tanah Dan Pencegahan Degradasi Lahan Kering (Studi Kasus Di PT. Agromar) - Selsi, Theresia Oktaviana (PUCUK : Jurnal Ilmu Tanaman, 2025)
The purpose of this study is to find effective methods in preventing erosion, increasing soil organic content, and improving soil structure in dryland. This research activity was carried out at PT. Agromar Maumere, Uneng City Village, Alok District, Sikka Regency. For this data collection technique, the author uses interview and observation methods. Meanwhile, secondary data is usually stored in documents that have become archives. Data sources are usually obtained from journals, past reports, company websites and other sources. This research activity includes observation of soil conditions, experiments with various soil conservation techniques such as making terraces, planting ground cover plants, or the use of mulch and the impact of these treatments on plant growth and soil quality. From the results of observations of soil conservation activities to prevent land degradation that already exists in PT. Agromar includes the use of mulch, the use of organic fertilizers and crop rotation. Soil conservation measures and prevention of dryland degradation are important efforts to maintain soil fertility. Soil conservation activities involve plant rotation techniques, the use of organic fertilizers and the use of mulch, to prevent erosion. Soil conservation activities that can be carried out are by using plastic mulch and adding organic materials for soil conservation efforts that are able to maintain soil chemical properties such as increasing the availability of organic C, total N, Kdd (carrying capacity), and Cadd (Acid Dissociation Capacity) and can maintain pH to remain stable in the neutral category. The use of mulch, crop rotation and the addition of soil organic matter can improve the physical properties of the soil both lowering BI and increasing soil porosity.